The Influence of Arabic Language Training (Daurah Arabiyah) and Arabic Day (Yaum Arabi) on the Arabic Language Skills of Students in the Arabic Language Education Program at IAIN Madura - Saputri, Diana Eka; Muis, Muhsin (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
The purpose of this study was to determine the effect of Daurah Arabiyah and Yaum Arabi on Arabic Language Skills of Madura IAIN Students. This research is a type of associative quantitative research. The object of this research is the students of the IAIN Madura Arabic Education Study Program semester 1, semester 3, semester 5, and semester 7. The sampling technique used is the simple random sampling technique, and the sample used is 200 students of the IAIN Arabic Language Education Study Program. Madura. The type of data used in this research is quantitative data. Sources of data in this study are primary data sources and secondary data sources. The method used in this study is the Classical Assumption Test and Hypothesis Test. Data collection techniques through questionnaires in the google form. The results of this study explain that Daurah Arabiyah has no effect the Arabic Language Skills of Madura IAIN Students with a significance value of 0.955. Yaumul Arabi has a positive and significant effect on the Arabic Language Skills of IAIN Madura Students with a significance value of 0.001. As well as Daurah Arabiyah and Yaum Arabi have a significant effect simultaneously on the Arabic Language Skills of Madura IAIN Students with a significance value of 0.002.